PERANCANGAN APLIKASI E-COMMERCE BERBASIS ANDROID PADA CALVCARE - Vidiani Aulia Fadiyawan (2022)
This research was conducted at a skincare sales store called calvcare, the calvcare store was established in 2019 which is located in the Tanjung Priok area. In the Calvcare sales process, namely, the lack of sales transaction media, especially for buyers who live far from the store so they cannot buy products directly. The purpose of this study is that sales at Calvcare stores can increase and make it easier for users to obtain product information sold at Calvcare stores and make purchase transactions anywhere and anytime. This research uses the prototype method and uses UML (Unified Modeling Language) and Design Figma modeling, and the design uses laragon, visual studio code, android studio, and database adminer. This research produces an android-based e-commerce application on calvcare. For similar research, it is recommended that the features of the application be designed according to the client's needs.